Cystic Endometrioma with Coexisting Fibroma Originating in a Supernumerary Ovary in the Rectovaginal Pouch - Daiki Ogishima; Asumi Sakaguchi; Hiroko Kodama; Kanako Ogura; Ayako Miwa; Yayoi Sugimori; Shozo Matuoka; Toshiharu Matsumoto (Case Reports in Obstetrics and Gynecology)
A supernumerary ovary is an exceedingly rare disorder, in which the structure containing ovarian tissue is located at some distance from the normally placed ovary. 16 cases of endometriosis or tumors originating in a supernumerary ovary have been published in the English literature, but no case of coexisting endometriosis and a tumor has been published. We present the case of a 40-year-old female with cystic endometrioma with coexisting fibroma originating in a supernumerary ovary in the rectovaginal pouch. The present case is the first to be reported with coexisting endometriosis and a tumor originating in a supernumerary ovary. Our experience with this case and the results of our previous studies of rectovaginal endometriosis indicated that the possibility of originating in a supernumerary ovary shall be examined in cases of cystic endometrioma in the rectovaginal pouch.